2011
DOI: 10.1089/thy.2010.0322
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Administration Induces Rat Liver Nrf2 Activation: Suppression byN-Acetylcysteine Pretreatment

Abstract: In vivo T(3) administration leads to a rapid and transient cytosol-to-nuclear translocation of liver Nrf2. This appears to be promoted by a redox-dependent mechanism as it is blocked by NAC. It may also be contributed by concomitant p38 activation, which in turn promoted Nrf2 phosphorylation. Nrf2 cytosol-to-nuclear translocation may represent a novel cytoprotective mechanism of T(3) to limit free radical or electrophile toxicity, as this would likely entail promoting thioredoxin production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 35 publications
4
42
1
Order By: Relevance
“…It is possible that the changes in antioxidant enzyme activities do not match changes in enzyme levels. Indeed, although it has been reported that T3 induces expression of peroxisomal proliferator activated receptor γ coactivator (PGC-1) (Venditti et al, 2009) and activation of nuclear transcription factor erythroid 2-related factor 2 (Nrf2) (Romanque et al, 2011), which regulate the expression of components of antioxidant system, we only found T3-linked increase in TrxR/PrX system activity.…”
Section: Tablecontrasting
confidence: 74%
“…It is possible that the changes in antioxidant enzyme activities do not match changes in enzyme levels. Indeed, although it has been reported that T3 induces expression of peroxisomal proliferator activated receptor γ coactivator (PGC-1) (Venditti et al, 2009) and activation of nuclear transcription factor erythroid 2-related factor 2 (Nrf2) (Romanque et al, 2011), which regulate the expression of components of antioxidant system, we only found T3-linked increase in TrxR/PrX system activity.…”
Section: Tablecontrasting
confidence: 74%
“…The use of this cell line was previously reported by us in Zhao et al [9]. Min6 cells (passage [38][39][40][41][42][43][44][45][46][47][48] were cultured in DMEM (25 mM glucose) supplemented with 10% heat-inactivated FBS, 100 IU/ml penicillin, 100 mg/ml streptomycin, and 50 mM β-mercaptoethanol in a humidified atmosphere of 95% air and 5%CO 2 . The culture medium was changed three times per week.…”
Section: Introductionmentioning
confidence: 99%
“…So, perhaps comedications affect the later common phases of drug-induced liver injury, including: cytoprotection, stress response (Han et al, 2013), regulation of injury and/or immune response (Han et al, 2013; Uetrecht and Naisbitt, 2013), and tissue repair. Comedications can favorably modulate the immune system (e.g., TNF-α inhibitors, glucocorticoids, opioids), liver injury/repair (e.g., ACE inhibitors/angiotensin II blockers) (Alisi et al, 2005; Suzuki et al, 2009a,b), and oxidative stress (e.g., folic acid, thyroid hormone) (Huang et al, 2001; Romanque et al, 2011), and thereby decrease liver injury. Other drugs and drug classes may reduce inflammation (e.g., coxibs, aspirin, anti-vitamin K) or protect cells from cellular injury: estrogens (Shimizu and Ito, 2007; Kozlov et al, 2010), mucolytics (Felix et al, 1996), and benzodiazepines (Carayon et al, 1996; Kunduzova et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Such drugs/drug classes include anti-TNFα, glucocorticoids, opioids (Roy and Loh, 1996; Peterson et al, 1998), anti-histamines (Okamoto et al, 2009), anti-muscarinic (Vacca et al, 2011), SSRIs (Maes, 2001), and beta2-adrenoreceptor agonists (Wang et al, 2009). Other drugs/drug classes are known to reduce inflammation [e.g., coxibs, aspirin, anti-vitamin K, TNF-alpha inhibitors, glucocorticoids] or protect cells from cellular injury [e.g., folic acids] (Huang et al, 2001), thyroid hormones (Romanque et al, 2011), estrogens (Shimizu and Ito, 2007; Kozlov et al, 2010), mucolytics (Felix et al, 1996), and benzodiazepines (Carayon et al, 1996; Kunduzova et al, 2004). Several drugs/drug classes may exert their impact via modulating repair [e.g., ACE-inhibitors, angiotensin II blockers, calcium blockers, antiadrenergics, thyroid hormones] (Garcia-Pagan et al, 1994; Alisi et al, 2005; Suzuki et al, 2009a,b) or epigenetic modification [i.e., hypo-methylation and/or histone acetylation, e.g., carboxamides, hydantoin, barbiturates, pyrazinamide, and isoniazid] (Poirier and Wise, 2003; Murata et al, 2007).…”
Section: Figmentioning
confidence: 99%